Pengembangan Aplikasi Mobile Pemesanan dan Pembayaran Makanan Berbasis Cloud Storage - Erico Darmawan Handoyo; Sulaeman Santoso; Daniel Jahja Surjawan (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
Most dining place or restaurant generally still uses manual food ordering process, the service will come to the customer to ask for the food to be ordered. However, during this soaring covid pandemic, the owners are afraid of the spread through waiters who come to customers. For this reason, an application will be made that can provide self-service food orders by customers without having to interact with waiters. Most digitalization efforts only focus on the client aspect of the ordering process and not on the processing of those orders (in the kitchen). This research looks to give an alternative digital ordering system that is integrated with not only the process on the client side but also on the kitchen side.